[tex]2 {(x + 5)}^{2} - {(x - 1)}^{2} - (x + 4)(x - 4)[/tex]
[tex] = 2( {x}^{2} + 2 \times x \times 5 + {5}^{2} ) - ( {x}^{2} - 2 \times x \times 1 + {1}^{2} ) - ( {x}^{2} - {4}^{2} )[/tex]
[tex] = 2( {x}^{2} + 10x + 25) - ( {x}^{2} - 2x + 1) - ( {x}^{2} - 16)[/tex]
[tex] = 2 \times {x}^{2} + 2 \times 10x + 2 \times 25 - {x}^{2} + 2x - 1 - {x}^{2} + 16[/tex]
[tex] = 2 {x}^{2} + 20x + 50 - {x}^{2} + 2x - 1 - {x}^{2} + 16[/tex]
[tex] = 2 {x}^{2} - {x}^{2} - {x}^{2} + 20x + 2x + 50 - 1 + 16[/tex]
[tex] = 22x + 65[/tex]
[tex] = > B) \: 22x + 65[/tex]